Nepal : Joint Staff Assessment of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2003)
The Joint Staff Assessment on Nepal's Poverty Reduction Strategy Paper (PRSP) highlights the PRSP process aimed to provide sustainable macroeconomic framework, improving governance and the overall policy environment. It reviews the execution of the envisaged programs, expenditure planning, public expenditure management system, and the effectiveness of the monitoring system. It also identifies some shortcomings of the PRSP that could be addressed over time and reflected in the annual progress reports to ensure that the strategy is fully effective and operational.